The psychology of communicating trust: consensual dependency of trust and knowledge sharing - Selvam, Rejina M. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Trust indicates positive effects on mental and social health in the work environment. In this study it was aimed to analyze the bidirectionality of trust and knowledge sharing variables over time. Results showed that there is a time pattern in the relationship between the two measures, where in time 1 (initial stage) participants have higher trust through knowledge sharing. In time 2 (middle stage) trust decreases and finally in time 3 (matured stage) it again increases. Finally, implications of the study and how knowledge sharing can be an antecedent to trust building atleast in the initial stage is discussed.